Comparison between Open Testicular Biopsy and Testicular Fine Needle Aspiration (TEFNA) Cytology in Obstructive Azoospermia - Zeeshan Ahmad Raza, Athar Mahmood, Humayun Saeed, Mudessar Rafaqat, Ismat Ullah, Muhammad Shahzad Anwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare open testicular biopsy and testicular fine needle aspiration (TEFNA) for spermatogenesis in terms of Johnsen’s scoring in patients with suspicion of obstructive azoospermia. Study Design: Comparative study. Place and Duration of Study: Department of Urology, Services Hospital, Lahore from 24th December 2018 to 23rd December 2019. Methodology: Forty males with primary infertility and azoospermia (in 3 consecutive reports) were enrolled. Males with normal testicular size and bilaterally palpable vas deference were investigated further regarding their hormone profile (serum FSH, LH, and Testosterone) and scrotal color Doppler ultrasound (CDUS). When hormones and scrotal ultrasound were found normal, appointment was given to patients for procedure, after complete discussion about their diagnosis and plan of management with possible complications. Both procedures; open testicular biopsy and testicular fine needle aspiration (TEFNA) were done simultaneously under local anesthesia. Specimen obtained from both procedures was sent for analysis of spermatogenesis in terms of Johnsen scoring. Patients were discharged after four hours with advice of daily dressing for five days and scrotal support for two weeks and oral Diclofenac Sodium 50mg twice daily after meals for three days. Results: The mean values of Johnsen scores were 7.7±2.8 in open biopsy while in TEFNA 9.9±0.95 and statistically significant (<0.05) results were found. Among 40 patients, 33(82.5%) patients showed spermatogenesis on open biopsy and 39(97.5%) on TEFNA. Sensitivity (Se), specificity (Sp), positive predictive value (PPV), negative predictive value (NPV) and accuracy of TEFNA in diagnosing spermatogenesis was 100%, 14.2%, 84.6, 100.0% and 85.0% respectively. Conclusion: Testicular fine needle aspiration is found to be a simple, reliable, and least invasive mode of diagnosing and management of azoospermia in adult males with minimal complications. Keywords: Open testicular biopsy, TEFNA, Infertility, Johnsen score